2022
DOI: 10.48550/arxiv.2201.07682
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cosmic Birefringence from Planck Data Release 4

P. Diego-Palazuelos,
J. R. Eskilt,
Y. Minami
et al.

Abstract: We search for the signature of parity-violating physics in the cosmic microwave background, called cosmic birefringence, using the Planck data release 4. We initially find a birefringence angle of β = 0.30 ± 0.11 (68% C.L.) for nearly full-sky data. The values of β decrease as we enlarge the Galactic mask, which can be interpreted as the effect of polarized foreground emission. Two independent ways to model this effect are used to mitigate the systematic impact on β for different sky fractions. We choose not t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 67 publications
2
16
0
Order By: Relevance
“…On the other hand, a smaller Galactic mask gave EB correlations with a fluctuating sign over multipoles . This mask dependence was confirmed by Diego-Palazuelos et al (2022) where a declining measurement of β was found when ignoring the intrinsic EB power spectra of the foreground using polarized data from the Planck public release 4 (PR4) (Planck Collaboration Int. LVII 2020), often called the "NPIPE" release.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…On the other hand, a smaller Galactic mask gave EB correlations with a fluctuating sign over multipoles . This mask dependence was confirmed by Diego-Palazuelos et al (2022) where a declining measurement of β was found when ignoring the intrinsic EB power spectra of the foreground using polarized data from the Planck public release 4 (PR4) (Planck Collaboration Int. LVII 2020), often called the "NPIPE" release.…”
Section: Introductionmentioning
confidence: 67%
“…As in previous work (Diego-Palazuelos et al 2022;Minami & Komatsu 2020a), we bin the spectra into groups of ∆ = 20 multipoles to minimize noise and cosmic variance. We focus only on high-multipoles by using min = 51 and max = 1490 which gives the number of bins N bins = 72.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations